Pengembangan Aplikasi Mobile Berbasis Android untuk Manajemen Antrian Bimbingan KP dan Proyek Akhir dengan Memanfaatkan Fitur Location Based Service - Nesya Anfasha Rosa; Shumaya Resty Ramadhani (Politeknik Negeri Batam, 2022)
Guidance is a procedure that must be done by students to get assistance and supervision in completing work practice reports and final assignments. This activity is carried out by holding meetings between students and the lecturers concerned. Students need to arrange a schedule by contacting the lecturer via communication media before conducting guidance. After arranging the schedule with the lecturer, students must be on time according to the predetermined schedule. Even though the tutoring schedule has been set, there are still students who come late. This causes guidance time to be wasted and other students do not get a schedule, so students are constrained in completing their reports. Therefore, an Android-based queue management application was developed by utilizing location-based service technology. This application uses priority-based queue management and location-based services that are used to detect lecturer geofence areas. Tests have been carried out on applications built using black-box testing techniques, with 100% results that all functional requirements have been successfully implemented. Likewise with the results of white-box testing that the program code has been executed with a percentage of 100%. In addition, testing using usability testing was also carried out with an average test percentage of 85.4% of respondents agreeing that the queuing application had met the criteria in the statement.